Juridic Aspects of Contract Renegotiation During the Covid-19 Pandemic as an Effort to Mitigate Risk and Loss in Business Activities - Galuh Kartiko; Andi Kusuma Indrawan; Dyah Metha Nurfitriasih (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study discusses the juridical aspect of contract renegotiation during the Covid 19 pandemic as an effort to mitigate risks and losses in business activities based on Presidential Decree Number 12 of 2020 concerning the Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 ( Covid-19 ) . Many business actors in the business world interpret the disaster as a force majeure, which is an extraordinary event that causes people to be unable to carry out their achievements due to an event beyond their capabilities. The research method used in this research is a normative legal research method. The results of this study are expected to provide debtors with an opportunity to resolve obstacles to their inability to pay installments by being allowed to apply for renegotiation or contract review in order to reach a mutual agreement. through the Regulation of the Financial Services Authority of the Republic of Indonesia Number ll/POJK.03/2020 concerning Stimulus The national economy which aims to maintain financial system stability and support economic growth.